2021
DOI: 10.16993/njtcg.28
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Multi-Professional Assemblages of Precision Guidance Producing the Resilient and Future-Oriented Citizen

Abstract: In this paper, we examined how EU-initiated 'integrated approach' to youth social exclusion is manifested in local contexts and in the ways in which youth problems and solutions come to be defined in particular schemes of thought. Inspired by assemblage theory we looked at local multi-professional youth guidance networks as assemblages consisting of multiple organisations, interests, steering, discourses, and knowledge formations. In this article we were especially interested in seeing which 'lines', understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Näissä tutkimuksissa keskiössä ovat olleet erityisesti numeerisen ja määrällisen tiedon keräämisen tuottamat ei-toivotut seuraukset. Tämän tutkimuksen tuloksissa esiin noussut työhyvinvoinnin lokeroituminen työntekijän yksityiselämään ja työterveyshuoltoon liittyväksi asiaksi, on ollut esillä muita koulutussektoreita koskevissa tutkimuksissa, joissa teemaa on tarkasteltu esimerkiksi nuorten syrjäytymisen näkökulmasta (Ecclestone & Brunila, 2015;Toiviainen & Brunila, 2021). Näissä tutkimuksissa on tunnistettu kulttuurisia oletuksia, joiden mukaan yksilön tulee itse ratkaista pulmansa sen sijaan, että ratkaisuja etsittäisiin sosiaalisista tai rakenteellisista yhteiskunnallisista tekijöistä.…”
Section: Kohti Laajempaa Käsitystä Varhaiskasvatuksen Ohjauksestaunclassified
“…Näissä tutkimuksissa keskiössä ovat olleet erityisesti numeerisen ja määrällisen tiedon keräämisen tuottamat ei-toivotut seuraukset. Tämän tutkimuksen tuloksissa esiin noussut työhyvinvoinnin lokeroituminen työntekijän yksityiselämään ja työterveyshuoltoon liittyväksi asiaksi, on ollut esillä muita koulutussektoreita koskevissa tutkimuksissa, joissa teemaa on tarkasteltu esimerkiksi nuorten syrjäytymisen näkökulmasta (Ecclestone & Brunila, 2015;Toiviainen & Brunila, 2021). Näissä tutkimuksissa on tunnistettu kulttuurisia oletuksia, joiden mukaan yksilön tulee itse ratkaista pulmansa sen sijaan, että ratkaisuja etsittäisiin sosiaalisista tai rakenteellisista yhteiskunnallisista tekijöistä.…”
Section: Kohti Laajempaa Käsitystä Varhaiskasvatuksen Ohjauksestaunclassified
“…In contrast, the guidance was undertaken as administrative control of the production-driven progress of CBT merely focuses on the achievement of outcomes guided by individualist-materialist neoliberal doctrines, regardless of the questions that uphold the meaning of subjectivity. The latter is described as behavioural governance when examined using the concept of precision guidance (Toivanen & Brunila, 2021).…”
Section: The Competency-tetris Metaphormentioning
confidence: 99%
“…Within counselling, we found that special educational needs in learning are related to the psychological trajectories of therapeutic habitation, viz. precision guidance (for conceptualisation, see Toivanen & Brunila, 2021). An example of this relationship was provided by two counsellors working with students with special educational needs:…”
Section: Fitting the Workforce Auction And Multi-professional Support...mentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in both policy and knowledge production in education governance are connected to the careful and meticulous disseminating of behavioural and personalised governance throughout these international, national and local assemblages (see Savage, 2020; Toiviainen and Brunila, 2021; Williamson, 2016). For example, in our two on-going research projects’ results, we have shown how the knowledge concerning young people’s education is circulated through various organisations and IGO’s, and how that knowledge becomes self-evident ‘truths’ in both national policy-making and everyday practises in youth education, counselling and guidance (Brunila et al, 2018; Mertanen et al, 2020a, 2020b, forthcoming).…”
Section: Future-proofing Education – the Emergence Of Precision Educa...mentioning
confidence: 99%